2014
DOI: 10.1111/sms.12240
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenic effects of swimming, jumping, and vibration on the protection of bone quality from disuse bone loss

Abstract: We assessed and compared the effects of swimming, jumping, and vibration therapies on the prevention of bone loss because of unloading. Eighty Wistar rats were randomly divided into eight groups: S, permanent hind limb-suspended rats; CON, control rats; S + Swim, unloading interrupted by swimming exercise; S + C(Swim), suspension interrupted by regular weight-bearing with the same duration as in the S + Swim protocol; S + Jump, unloading interrupted by jumping exercise; S + C(Jump), suspension interrupted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 40 publications
3
37
0
2
Order By: Relevance
“…The tibia of Wistar rats is one of the most used bones in orthopedic research 6 because it is easily accessed and presents a standard morphology that is representative of a typical long bone. To the best of our knowledge, a detailed study of its growth in relation to BM increase has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The tibia of Wistar rats is one of the most used bones in orthopedic research 6 because it is easily accessed and presents a standard morphology that is representative of a typical long bone. To the best of our knowledge, a detailed study of its growth in relation to BM increase has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have noted that different pressures and hits when swimming can cause another type of pressure or resistance on the bone. Falcai et al (2015) found that all three training programs in swimming, jumping, and vibration significantly increased bone mass, bone strength, bone formation, and the serum levels of markers of bone formation in Wistar rats [33]. Accordingly, prescribed exercises should be designed depending on the level of tolerance of each patient, especially those at risk of osteoporosis such as those who use inhaled or systemic corticosteroids [34].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium deposition in bone is partly regulated by the mechanical stress to which the bone is subjected 2 . Although the mechanism involved in bone anabolism is not yet completely clear, it is known that a mechanical stimulus acts both in the inhibition of bone resorption through the action of NO (nitric acid), which promotes osteoclast inhibition, and in bone synthesis by increasing the intracellular calcium in osteoblasts and serum levels of IGF-1, factors that increase BMD and bone strength 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exercise promotes metabolic and hormonal alterations that also stimulate the synthesis of calcium in bone tissue [15][16][17] . Thus, the aquatic exercise-induced increase in mineral density (ET8 group) could be explained by the mechanical stress caused by the tendon traction on the bones during muscle contraction, together with the metabolic and hormonal alterations caused by exercise.…”
Section: Discussionmentioning
confidence: 99%